Evaluation of rice (Oryza sativa L.) genotypes for cold tolerance at seedling stage - Sumayya, K; Rajanna, M P; Deepak, C A; Shivakumar, KV; Denesh, GR (ORYZA-An International Journal of Rice, 2020)
Cold tolerance during germination is important for ensuring fast and uniform crop establishment. Rice plants are injured at the seedling stage when they are grown in early spring in temperate or subtropical environments. The productivity of rice is particularly low during spring due to cold, which is an important abiotic constraint, where low temperature prevails below 18 ºC. The present study was taken up to evaluate cold tolerance in 86 rice genotypes based on seed and seedling parameters as per Cruz and Milach (2004). Seeds were germinated under two conditions i.e.,160C for 28 days (cold) and 280C for 7 days (control).The genotypes showed highly significant differences forparameters such as germination (%), germination index (%), percentage of seeds with coleoptile superior to 5 mm (PERCOL), percentage of reduction in coleoptile length (REDCOL) and coleoptile regrowth (COLREG, cm).Both REDCOL and COLREG seem to be the most adequate characteristics to be used to evaluate cold tolerance during the germination period in rice. Among those genotypes, AC 35548, JBT 37/164, PS 353, KMP-175 andThanu were adjudged as promising when screened for cold tolerance under laboratory conditions based on the aforementioned parameters.